RETRACTED: Eco-consumer standards for people with complex purchasing behaviour - Luneva Elena A.; Rebrova Natalia P.; Frik Olga V. (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001